?? ouro! A percep????o do consumidor em rela????o aos patrocinadores dos comit??s ol??mpico e paral??mpico brasileiros - Marques, Rui David (2015)
This research proposed an investigation to analyse the perception of spectators/consumers about the sponsorships in the Brazilian Olympic and Paralympic sports and verify if there are similarities in the perception of consumers about the sponsorships of the two main sport organizations in Brazil: the Brazilian Olympic Committee (COB) and the Brazilian Paralympic Committee (CPB). The goal was to understand if exits differences in the perception of the spectator/consumer about the motivation of these sponsors when supporting these high performance Brazilian sport organizations. Concepts about sport marketing, sport sponsorship and sport consumer perception were addressed in the research. This was accomplished though a secondary data research, through a survey with direct questions, multiple choice questions and Likert scales sent through internet instruments: email and social media used to deliver the survey to respondents. Factorial analysis was used to test the used constructs and Chi-Test and T-Test to analyse and test the hypothesis. The analisys of the results show that the consumer perception about the sponsors of both organizations is similar, but exists a canibalization between the sponsors of sport organizations.